KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PEMBELAJARAN DI ERA PANDEMI COVID 19 - Siti Muawanatul Hasanah (INCARE, International Journal of Educational Resources, 2020)
School has a function as an agent of change whose job is to build students to become human beings who have faith and are devoted to God, virtuous, healthy, knowledgeable, capable, creative, independent, being a good citizen, able solve the problems they face and become a solution for themselves, and society as a whole. To achieve the goals of education, the principal's active role as a leader and manager is needed in creating quality and superior schools. In this role the principal is expected to have work targets in realizing the vision and mission of the school. For this reason, the quality of education as one of the outputs will become a benchmark for each school as part of the principal's leadership in developing the quality of existing education. The quality of a school can be seen from the process along with the results in teaching and learning activities carried out. Teaching and learning activities remain a priority that must be maintained, developed, and carried out well regardless of the conditions. Like today, where Indonesia has experienced the Covid-19 pandemic since March to date, certainly many aspects have changed due to this pandemic, especially related to educational activities in Indonesia. For this reason, principals are expected to be able to improve the quality of learning in this pandemic era where face-to-face learning is not permitted in the school environment, thus requiring schools to create distance learning that does not reduce the value of conventional learning so that the quality of the learning process can be maintained and implemented properly.